posted by Nicole-Marie on .
We had a substitute in math on friday and we got a worksheet, but he didn't explain how to do it very well. Could someone work out a problem for me?
1. (2b^3)^3 * 3(b^-4)^2 =
I have no clue how to do this. The answer key says it is 24b^2 but I can't get that
Oh wait, the answer is just 24b. I wrote the wrong answer. But I can't get that either.
(2b^3)^3 * 3(b^-4)^2
step #1) = 8b^9 * 3b^-8
step #2) = 24b
step 1: (2^3 is 8, b^3^3 = b^9, b^-4^2 = b^-8)
step 2: Multiply the coefficients (8*3=24). Muliply the b terms: b^9 * b^-8 = b^1 = b